INVENTARISASI IKAN DI SUNGAI LEMATANG KECAMATAN RAMBANG DANGKU KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Dian Mutiara; Lela Fitrianti (Universitas PGRI Palembang, 2011)
ABSTRACTThe report result about fishs inventaritation in Lematang river at RambangDangku district South Sumatera Province. The research to study fishs at Lematang river at Rambang Dangku district South Sumatera Province. The research was conducted between Januari-Februari 2011. This research utilited the direct observation method during two week. The result on the research geted 5 Orders, 17 Familiy, and 35 Species.Key words : identification,klasification, fish, species, Lematang river.